EU Action Plan Against Disinformation: Public Authorities, Platforms and the People - Kouroutakis, Antonios (SSRN, 2020)
In democracies, people (demos in Greek) hold the power (kratos in Greek). When people elect their representatives from a number of candidates, such power is temporarily transferred to their elected representatives. Thus, the quintessence of democracy is a system of trust and accountability. Such power is returned to the people every time elections are held and people periodically evaluate their representatives and hold them accountable for their actions and omissions. If people are not satisfied with their representatives, they can always replace them with their competitors. For democracy to function in a proper manner, it is important that people are able to actively participate and vote based on trustworthy, accurate and complete information. But this system of trust is distorted by disinformation which became a fast-paced and widespread phenomenon. A foriori, during electoral periods, disinformation might have a decisive impact on the electoral result. A number of incidents of orchestrated disinformation around the world, alarmed the policy makers in the EU ahead of the European Parliament elections in May 2019 and the EU Action Plan Against Disinformation was adopted. This Action Plan is the most concrete and specific initiative on the matter. It is a modest regulatory intervention, based on soft law and self-regulation. As it is subject to a 12 month sunset clause, this marked its experimental nature and the EU Commission’s effort to monitor closely its application. The success of the action plan was based on the cooperation of the public authorities, of the platforms and the people. In substance, it was focused on four core areas: first on the improved detection of disinformation, second on the coordinated responses of disinformation, third on the cooperation with online platforms and the industry, and finally on the raising awareness and building resilience amongst citizens.
Keywords: Disinformation; EU Action Plan; Self-regulation; 59 Ciencia Política; ODS 16 - Paz, justicia e instituciones sólidas